2008
DOI: 10.1590/s1678-77572008000300006
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal dental care: evaluation of professional knowledge of obstetricians and dentists in the cities of Londrina/PR and Bauru/SP, Brazil, 2004

Abstract: The purpose of this study was to assess the current knowledge and recommendations of obstetricians and dentists as to the dental care to pregnant patients in the cities of Londrina/PR and Bauru/SP, Brazil. Questionnaires were distributed to professionals of both cities, arguing on the following issues: oral health during pregnancy; contact between prenatal care and dental care providers; prenatal fluoride supplementation; selection of therapeutic agents for local anesthesia, pain control and treatment of infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
3
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 21 publications
5
58
3
7
Order By: Relevance
“…16 The others general, prenatal care practitioners and dentists appear to be globally less aware of this link. 16,19,22,29 Interestingly, our results showed that less experienced obstetricians/gynecologists were less conscious of such a relationship than more experienced practitioners. Similarly, a study that assessed knowledge of physicians on interactions between periodontal disease and diabetes showed that experience is associate with a better knowledge on periodontal diseases -systemic interactions.…”
Section: Discussionmentioning
confidence: 67%
“…16 The others general, prenatal care practitioners and dentists appear to be globally less aware of this link. 16,19,22,29 Interestingly, our results showed that less experienced obstetricians/gynecologists were less conscious of such a relationship than more experienced practitioners. Similarly, a study that assessed knowledge of physicians on interactions between periodontal disease and diabetes showed that experience is associate with a better knowledge on periodontal diseases -systemic interactions.…”
Section: Discussionmentioning
confidence: 67%
“…Forty six (17.4%) of the dental surgeons were in a practice to take diagnostic radiograph in third trimester.Braimoh O et al [19] reported that 48(64.9%) of the dental surgeons knew that dental radiograph could be taken at any trimester in pregnancy and 44 (60%) of dental surgeons knew the best time to take dental radiograph was the second trimester of pregnancy. Zanata et al [20] reported that 16.2% and 37.8%, of the dental surgeons knew that dental radiograph was safe throughout in pregnancy and is best taken in second trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Zanata et al [20] reported that 38.7% of dental surgeons indicated that all types of radiography should be taken after the first trimester and only 25.5% of dental surgeons correctly knew that radiography is better to be postponed until the second trimester of pregnancy and that only 16.2% of dental surgeons allowed women for dental radiography throughout their pregnancy.About 89.1% of dental surgeons acknowledged the feasibility of three types of radiography on the condition that the safety rules are observed.…”
Section: Discussionmentioning
confidence: 99%
“…Durante a gestação, ocorre maior vascularização da cavidade oral devido à elevação nos níveis de progesterona e estrogênio, ocasionando o aumento da permeabilidade vascular e alterações na produção de colágeno, tornando a gengiva mais suscetível a infecções e ao biofilme bacteriano (19) . Essa condição também torna a gestante vulnerável a outros acometimentos, como diabetes mellitus gestacional (20) .…”
Section: Discussionunclassified